TINDAKAN PROVOKATIF SPANYOL MENEKAN INGGRIS DI WILAYAH KEDAULATANYA DI GIBRALTAR - Abror, Muhammad Yusuf; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research analyzes the reason of Spain preassured England over sovereignty of Gibraltar. This research want to know why did Spain keep on preassuring Gibraltar. The small region on point of Europe has much values such as economic, geopolitic and tourism. Those values made England and Spain had conflict. This is the reason why the writer interested in this research. This dispute started when Spain transfered sovereignty of Gibraltar to England in Spanish Succession War. Spain dispute Gibraltar from England because it had much potentials and very strategic. As the consequence, Gibraltar made twice referendum; on 1967 and 2002. The result of the referendum was Gibraltar people continued to live under England and rejected be apart of Spain. In another side, Spain preassure Gibraltar because Spain believed that Gibraltar as the main income for Spain in tax and fishing sector. Spain got protest about so much smuggling of tobacco in border Gibraltar-Spain and sink spiked concrete blocks into the sea by Gibraltar. This is reason why Spain lose out income from smuggling of tobacco and fisherman can not fishing on Algeciras Bay/ Gibraltar Bay. In this research writer using theory of Kenneth Waltz; Three Image. The Theory has three level analysis, that is individual, state and international system. Writer using level analysis of state, because this conflict involve two state. This study used methode of explanation, that is method to explain the problem in a particular and method library research, such as books, journals, magazine, media electronic, and the other source. The research showed Spain keep on preassureGibraltar,that is provocate on border of the sea (Algeciras Bay/ Gibraltar Bay), push down borderland, threat a â‚¬50 (67) charge on crossings borderland and threat to close air of Spain for Gibraltar flight.These is all of provocate about the economic.Keyword: Dispute of Gibraltar, Utrech Treaty 1713, referendum, smuggling of tobacco, sink spiked concrete blocks into the sea, lose out income of Spain, provocated, Three Image Theory.